Active vibration control responses of a smart microshell reinforced with graphene nanoplatelets and subjected to external force. Issue 11 (13th September 2022) - Ma, Lianghua; Liu, Xiaoliang; Shavalipour, Aghil
Abstract: Smart control and dynamic investigation of a graphene nanoplatelets composite (GPLRC) cylindrical microshell surrounded by a piezoelectric layer as actuator and sensor based on a numerical solution method called generalized differential quadrature method are presented for the first time. The current structure is under an external load. The strains and stresses can be determined through via the first-order shear deformable theory. For accessing to various mass densities, thermal expansion as well as Poisson ratio, the rule of mixture is applied, although, a modified Halpin–Tsai theory is used for obtaining the module of elasticity. The external voltage is applied to the sensor layer, while a proportional-derivative (PD) controller has been utilized for controlling output of sensor. GPLRC's boundary conditions are derived through governing equations of the cylindrical microshell using energy method known as Hamilton's principle. The outcomes show that the PD controller, viscoelastic foundation, slenderness factor ( L / R ), external voltage, and GPL's weight fraction have a considerable impact on the amplitude, and vibration behavior of a smart GPLRC cylindrical microshell. As an applicable result in related industries, the parameter and consideration of the PD controller have a positive effect on the static and dynamic behaviors of the microstructure subjected to external load.